Extensive Reading in Improving Reading Motivation: A Students’ Perspective - Permatasari, Alfelia Nugky; Wienanda, Wahyu Kartika (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. Students nowadays are accustomed to vast yet short information coming from various digital platforms. This affects their concentration span in a negative way and causes a difficulty in focus, including reading a longer text. This study aims to investigate how extensive reading practice improves students’ motivation in reading. Specifically, this study aims to elaborate students’ experience in English for General Reading subject, how far the extensive reading practice can increase students’ reading efficacy, and what impact the practice gives to students’ curiosity on specific topics. The finding is expected to uncover new possible ways, which educators can implement to match varied learning needs by optimizing the effectiveness of the activity. Data of this phenomenology study was taken through observation during the class and online questionnaire as the class evaluation after the class has finished. A number of semi-structured interviews were also conducted to a number of students to gain a deeper understanding of the phenomena. The interviews are transcribed, coded, and analysed using thematic analysis. This study found that extensive reading practice helps students improving their reading motivation in general, through enjoyment on familiar subjects, reading efficacy, as well as engagement on new topics.Keywords: Extensive Reading, Reading Motivation, Phenomenology, Student’s Perspective